Comparative pathogenesis of rabies in bats and carnivores, and implications for spillover to humans. Issue 4 (April 2018) - Begeman, Lineke; GeurtsvanKessel, Corine; Finke, Stefan; Freuling, Conrad M; Koopmans, Marion; Müller, Thomas; Ruigrok, Tom J H; Kuiken, Thijs
Summary: Bat-acquired rabies is becoming increasingly common, and its diagnosis could be missed partly because its clinical presentation differs from that of dog-acquired rabies. We reviewed the scientific literature to compare the pathogenesis of rabies in bats and carnivores—including dogs—and related this pathogenesis to differences in the clinical presentation of bat-acquired and dog-acquired rabies in human beings. For bat-acquired rabies, we found that the histological site of exposure is usually limited to the skin, the anatomical site of exposure is more commonly the face, and the virus might be more adapted for entry via the skin than for dog-acquired rabies. These factors could help to explain several differences in clinical presentation between individuals with bat-acquired and those with dog-acquired rabies. A better understanding of these differences should improve the recording of a patient's history, enable drawing up of a more sophisticated list of clinical characteristics, and therefore obtain an earlier diagnosis of rabies after contact with a bat or carnivore that has rabies.